Live imaging of root-bacteria interactions in a microfluidics setup - Massalha, Hassan; Korenblum, Elisa; Malitsky, Sergey; Shapiro, Orr H; Aharoni, Asaph (Proceedings of the National Academy of Sciences - PNAS, 2017)
Plant roots play a dominant role in shaping the rhizosphere, the environment in which interaction with diverse microorganisms occurs. Tracking the dynamics of root-microbe interactions at high spatial resolution is currently limited because of methodological intricacy. Here, we describe a microfluidics-based approach enabling direct imaging of root-bacteria interactions in real time. The microfluidic device, which we termed tracking root interactions system (TRIS), consists of nine independent chambers that can be monitored in parallel. The principal assay reported here monitors behavior of fluorescently labeled as it colonizes the root of within the TRIS device. Our results show a distinct chemotactic behavior of toward a particular root segment, which we identify as the root elongation zone, followed by rapid colonization of that same segment over the first 6 h of root-bacteria interaction. Using dual inoculation experiments, we further show active exclusion of cells from the root surface after colonization, suggesting a possible protection mechanism against root pathogens. Furthermore, we assembled a double-channel TRIS device that allows simultaneous tracking of two root systems in one chamber and performed real-time monitoring of bacterial preference between WT and mutant root genotypes. Thus, the TRIS microfluidics device provides unique insights into the microscale microbial ecology of the complex root microenvironment and is, therefore, likely to enhance the current rate of discoveries in this momentous field of research.